2015
DOI: 10.1186/s40648-015-0030-2
|View full text |Cite
|
Sign up to set email alerts
|

Active modification of the environment by a robot with construction abilities

Abstract: Field robots are widely used to accomplish a variety of tasks in many different fields. However, setting of the locomotive ability of these robots at the design phase may prevent the traversal of unknown rough terrain. To address this shortcoming of existing robots, we designed a robot that is able to modify its environment by using polyurethane foam to construct auxiliary structures to facilitate movement across previously impassable terrain. Two robots were implemented with the ability to eject one-and two-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…Generally combining mobile platforms with conventional industrial robots, these compound setups have been predominantly demonstrated with standardized building components (Dörfler et al 2016) or industrially produced chemical products (Keating et al 2014). Recent research has demonstrated the potential of robotic systems to construct auxiliary structures to achieve and maintain navigability in previously unknown or untraversable terrain, but these experiments have only been demonstrated at a small scale, and do not make use of naturally occurring found construction materials (like stones), but instead use compliant bags (Saboia et al 2019) or polyurethane foam (Fujisawa et al 2015) to homogenize the irregularities in their environment.…”
Section: Related Workmentioning
confidence: 99%
“…Generally combining mobile platforms with conventional industrial robots, these compound setups have been predominantly demonstrated with standardized building components (Dörfler et al 2016) or industrially produced chemical products (Keating et al 2014). Recent research has demonstrated the potential of robotic systems to construct auxiliary structures to achieve and maintain navigability in previously unknown or untraversable terrain, but these experiments have only been demonstrated at a small scale, and do not make use of naturally occurring found construction materials (like stones), but instead use compliant bags (Saboia et al 2019) or polyurethane foam (Fujisawa et al 2015) to homogenize the irregularities in their environment.…”
Section: Related Workmentioning
confidence: 99%
“…Compressive strengths of over 2M P a are possible, so that the solidified foam can easily support the weight of a human standing on it. Expansion ratios of over 30× the original volume are viable, meaning that 25dm 3 of solidified foam can be generated from just 0.84dm 3 of the two part liquid constituents [9]. These values depend largely on the mixing style and have been recorded through testing on the proposed system, as discussed in section III-B.…”
Section: A Polyurethane Foammentioning
confidence: 99%
“…The foam in its final state is closed-cell, water-proof and lighter than water yet, as mentioned, still strong enough to support the weight of a human climbing thereon. Additionally, these foams adhere to a wide variety of materials including wood, iron, and concrete, among others [9]. Based on these characteristics, this material is suitable for use in disaster scenarios in real-time.…”
Section: A Polyurethane Foammentioning
confidence: 99%
See 2 more Smart Citations